Allelopathic potential of indigenous Bangladeshi rice varieties. Issue 3 (29th September 2016) - Masum, Sheikh M.; Hossain, Mohammad Amzad; Akamine, Hikaru; Sakagami, Jun‐Ichi; Bhowmik, Prasanta C.
Abstract : A series of experiments was conducted in the laboratory and greenhouse of the Subtropical Field Science Center, University of the Ryukyus, Japan, from April to October 2015 to assess the allelopathic potential of 50 indigenous Bangladeshi rice varieties by using the donor–receiver bioassay, equal compartment agar method (ECAM), plant residue extract method and pot culture method. Lettuce ( Lactuca sativa L.), cress ( Lepidium sativum L.), radish ( Raphanus sativus L.), barnyard grass ( Echinochloa crus‐galli L. Beauv.) and jungle rice ( Echinochloa colona L.) were used as the test plants. The highest inhibition effect was given by Boterswar, while the stimulating effect was given by Kartikbalam and Panbira in the donor–receiver bioassay and ECAM tests. Boterswar, Goria, Biron and Kartiksail were selected as the highest allelopathic‐potential varieties by the donor–receiver bioassay and ECAM. In the methanol extract test, Boterswar gave the strongest inhibitory effect on both barnyard grass and jungle rice, while Kartiksail gave the highest inhibitory effect on the jungle rice shoot. The growth parameters and total dry matter of barnyard grass in the greenhouse pot experiment were significantly reduced as a result of the application of aqueous extracts of the selected rice varieties, which was similar to the results of the laboratory experiments. The varieties of Boterswar, Goria, Biron and Kartiksail were selected as the most allelopathic among the 50 indigenous Bangladeshi rice varieties. These rice varieties could be used for the isolation and identification of allelochemicals and to further develop new varieties that are tolerant to weeds.